Faunistic survey of terrestrial isopods (Isopoda: Oniscidea) in the Boč Massif area - Blanka Ravnjak; Ivan Kos (Natura Sloveniae)
In 2005, terrestrial isopods were sampled in the Boč Massif area, eastern Slovenia, and their fauna compared at five different sampling sites: forest on dolomite, forest on limestone, thermophilous forest, young stage forest and extensive meadow. Two sampling methods were used: hand collecting and quadrate soil sampling with a subsequent heat extraction of animals. The highest species diversity (8 species) was recorded in the forest on dolomite and in young stage forest. No isopod species were found in samples from the extensive meadow. In the entire study area we recorded 12 different terrestrial isopod species and caught 109 specimens in total. The research brought new data on the distribution of two quite poorly known species in Slovenia: the Trachelipus razzauti and Haplophthalmus abbreviatus.